MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN 1 SAMPAI 5 MELALUI MEDIA FLASH CARD BAGI SISWA TUNAGRAHITA SEDANG - Ade Satriana; Markis Yunus; Fatmawati Fatmawati (Universitas Negeri Padang, 2013)
This study begins with students mental retardation issue was class D1 SLB Tanjungpinang Affairs, students are not familiar symbol numbers 1 through 5. So to solve this problem, researchers as classroom teachers using flash media card.Methodology This study uses classroom action research organized in the farm collaborate with peers. Subjects in this study were teachers and six students were mental retardation. Data collected by the Observation techniques, test and analyzed with qualitative data analysis techniques. Action to implementation is done in two cycles with ten meetings. At the end of the cycle I and II evaluation.Evaluation results show the ability of the end of the first cycle students to know symbol numbers reached the 51% criterion has not reached the minimum tasan ketun-63. In order for the results obtained in line with expectations, the activities should be continued on the second cycle. After the extension of the action and an evaluation at the end of the second cycle, the data obtained average grade increased to 85%. Based on the analysis of the results of the evaluation cycle I and II, proving that the use of flash media cards can increase the ability to recognize the symbol numbers 1 through 5 for students tunagrahita SLB class D1 State Tanjungpinang. Researchers suggest that the use of flash media cards can be an alternative choice for teachers as well as other media.